Tunable Fano resonances via optomechanical effect and gain–loss ratio in coupled microresonators. (18th September 2018) - Ziauddin,; Jamil, Rabia; Chaung, You-Lin; Rahmatullah,
Abstract: We propose a system consisting of two coupled optical whispering-gallery-mode (WGM) microresonators to investigate the Fano resonances of the output probe field. The WGM microresonators are driven coherently by a strong pump field and a weak probe field via tapered fibers (Peng et al 2014 Nat. Phys .10 394). By making one of the resonators optomechanical and properly adjusting the coupling strength between the microresonators, we tune the Fano line shapes by varying the optomechanical strength. It is found that Fano line shapes appear on introducing optomechanical effects into the system. Interestingly enough, the gain–loss ratio in the proposed system has a key role in tuning a single Fano line shape to double. For the -symmetric phase, we investigate a more prominent double Fano line shape. The adjustment from single Fano line shape to double via the gain–loss ratio is the major part of this work. Our results can be used for all-optical switching and high-sensitivity sensing.